(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To compare liquid-based cytology (LBC) and conventional Pap smear (CPS) in the detection of cervical cancer. Study Design: This was a cross-sectional study. Place and Duration of Study: This research was conducted at Liaquat University of Medical and Health Sciences Jamshoro from February 2025 to February 2026 Methods: Total 200 women aged 20-65 years with symptomatic presentation indicative of cervical pathology were included. CPS and LBC were used to collect cervical samples. Smear adequacy, endocervical cell presence, and cytological findings were assessed. Histopathological findings were used as a reference standard where available. SPSS version 26 was used to analyze the data. The sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were computed. The p-value of <0.05 was found to be statistically significant. Results: The mean age of participants was 44.9±6.5 years. LBC demonstrated a significantly higher rate of satisfactory smears (n=188, 94.0%) compared to CPS (n=166, 83.0%) (p<0.001). Endocervical cells were more frequently detected in LBC (n=112, 56.0%) than CPS (n=78, 39.0%) (p<0.001). For LSIL, LBC had higher sensitivity (88.0%) and specificity (99.0%) compared to CPS (72.0% and 98.0%). In the case of HSIL, LBC showed better sensitivity (77.0% and 99.0%) and specificity (62.0% and 98.5%) than CPS. PPV and NPV were consistently higher with LBC. Conclusion: LBC demonstrated better performance than CPS in terms of smear adequacy and diagnostic accuracy. It may be considered a more effective method for cervical cancer screening. Additional large-scale studies using HPV testing are recommended.